P472 Changes in colectomy for Ulcerative Colitis during the last two decades: an in-depth retrospective analysis. (21st January 2022) - Le Cosquer, G; Capirchio, L; Rivière, P; de Suray, N; Poullenot, F; De Vroey, B; Berger, A; Denis, M A; Zerbib, F; Bachmann, R; Remue, C; Celerier, B; et al.
Abstract: Background: The management of ulcerative colitis (UC) has been improved due to progresses in medical and surgical practices during the past twenty years. Yet the impact of new therapies on the evolution of the three colectomy's indications in UC (severe acute colitis, refractory ulcerative colitis and (pre-)neoplastic complication) is still not well established. The aim of this study was to compare the evolution of the surgical indications within the last two decades. Methods: This was an observational retrospective study carried out in two tertiary hospitals. All patients with UC who underwent total or segmental colectomy between 2001 and 2020 were included, without age restriction. Two periods were compared: 2001–2010 and 2011–2020. Endpoints were to compare the colectomy indications, patients' characteristics, surgical procedures, and rates of postoperative complication between the two cohorts. Results: Among the 286 patients included (57% were men; median age of 40 years; 60.5% of extensive and 35.7% of distal colitis), 87 (30.4%) underwent colectomy in 2001–2010 and 199 patients (69.6%) in 2011–2020. Patients' characteristics were similar between the two periods, including duration of UC and the severity according to the global Mayo score. Colectomy rate for refractory UC significantly decreased over time (n=119) (50.6% vs. 37.7%; p=0.042), while it increased for acute severe colitis (n=116) (36.8% vs. 42.2%; p=0.390) and (pre-)neoplastic indication (n=51) (12.6% vs. 20.1%; p=0.130) (Figure 1). Regarding surgery, there was an increased use of laparoscopic colectomy (47.7% vs. 81.4%; p<0.001) during the latter period and the median length of stay in hospital after surgery has decreased from 13 to 10 days (p=0, 098). There were less early (12.6% vs. 5.5%; p=0.038) and late severe complications (1.6% vs. 0.8%; p< 0.001) and less surgical revisions (38.6% vs. 19.5%; p<0.001) without change on 30-day mortality rate (2.3% vs. 1%; p=0.391). The rate of extraintestinal postoperative infections (especially urinary, pulmonary and catheters infections) increased during the second period (27% vs; 45.7%; p=0.018). As expected, the mean number of past biotherapies was higher during the second period (1.2 versus 0.6; p<0.001), as well as the rate of pre-operative exposition to TNFα antagonists (68.4% vs. 50.6%; p=0.016). Conclusion: The rate of surgery for refractory colitis has significantly decreased while the rate of colectomy for cancer and acute severe colitis has risen during the last twenty years. In the same time, surgical technics have changed with more laparoscopic surgeries associated with a reduction of postoperative morbidity despite the larger use of biotherapies.